Effects of melatonin supplementation on oxidative stress, and inflammatory biomarkers in diabetic patients with chronic kidney disease: a double-blind, randomized controlled trial - Sara Sadeghi; Amirahmad Nassiri; Monir Sadat Hakemi; Fatemeh Hosseini; Fatemeh Pourrezagholie; Fatemeh Naeini; Aylar Nadiri Niri; Hossein Imani; Hamed Mohammadi (BMC Nutrition)
Abstract Background and objectives Chronic kidney disease (CKD) is a progressive illness linked to higher rates of morbidity and death. One of the main causes of CKD is diabetes mellitus (DM), and oxidative stress is essential to the disease's development. It has been demonstrated that the natural antioxidant melatonin reduces inflammation and oxidative damage in renal tissues. Given the lack of robust evidence, this double-blind clinical trial sought to investigate the effects of melatonin supplementation on oxidative stress and inflammatory markers in diabetic CKD patients. Materials and methods This trial included 41 diabetic patients with CKD (stages 3–4) from Shariati Hospital, Tehran, Iran. For ten weeks, participants were randomized to receive either a placebo or 5 mg of melatonin twice a day. Baseline characteristics, dietary intake, physical activity, and anthropometric measurements were recorded. Oxidative stress (TAC, TOS, MDA) and inflammatory markers (IL-6, hs-CRP) were measured before and after the intervention. Statistical analysis was performed using SPSS, with significance set at p < 0.05. Results The 10-week trial was completed by 41 participants in total, and no adverse effects were noted. Dietary intake, physical activity, and anthropometric parameters did not significantly differ between the melatonin and control groups in baseline characteristics. Melatonin supplementation decreased oxidative stress and inflammatory biomarkers, including hs-CRP, MDA, TOS, and IL-6. However, these changes were not statistically significant. Conclusion Our study showed that melatonin supplementation did not significantly affect oxidative stress or inflammatory markers, including TAC, TOS, MDA, IL-6, and hs-CRP, in diabetic patients with CKD. Despite a decrement in TOS, MDA, IL-6, and hs-CRP levels after 10 weeks, this was not statistically significant. Further studies with larger sample sizes, greater dosages, and longer follow-up periods are recommended.